(3GdOdjd ZjQ GdQSej (B:s (3cja JMUd Ydi eG JSJMb (B/s - (3QjJT, LGShf Q(B.s; (3ecJHI LQjQ (B((3GdQjGV(B)s ((3GdQjGV (B:s (3ecJHI LQjQ,s, 2001)
(3jbOe gPG GdcJGH ddehXajf GdCPcjGA djYdege Cj GdCSGdjH GdfGLMI ddJaGhV hGdCNQi GdaGTdI(B.s
Keywords: (3GdfLGM GdTNUjs